Static and dynamic cultivation of bone marrow stromal cells on biphasic calcium phosphate scaffolds derived from an indirect rapid prototyping technique - Detsch, Rainer; et al. (Journal of Materials Science: Materials in Medicine, 2010)
The adequate regeneration of large bone defects is still a major problem in orthopaedic surgery. Synthetic bone substitute materials have to be biocompatible, biodegradable, osteoconductive and processable into macroporous scaffolds tailored to the patient specific defect. Hydroxyapatite (HA) and tricalcium phosphate (TCP) as well as mixtures of both phases, biphasic calcium phosphate ceramics (BCP), meet all these requirements and are considered to be optimal synthetic bone substitute materials. Rapid prototyping (RP) can be applied to manufacture scaffolds, meeting the criteria required to ensure bone ingrowth such as high porosity and defined pore characteristics. Such scaffolds can be used for bone tissue engineering (BTE), a concept based on the cultivation of osteogenic cells on osteoconductive scaffolds. In this study, scaffolds with interconnecting macroporosity were manufactured from HA, TCP and BCP (60 wt% HA) using an indirect rapid prototyping technique involving wax ink-jet printing. ST-2 bone marrow stromal cells (BMSCs) were seeded onto the scaffolds and cultivated for 17 days under either static or dynamic culture conditions and osteogenic stimulation. While cell number within the scaffold pore system decreased in case of static conditions, dynamic cultivation allowed homogeneous cell growth even within deep pores of large (1,440 mm) scaffolds. Osteogenic cell differentiation was most advanced on BCP scaffolds in both culture systems, while cells cultured under perfusion conditions were generally more differentiated after 17 days. Therefore, scaffolds manufactured from BCP ceramic and seeded with BMSCs using a dynamic culture system are the method of choice for bone tissue engineering. © 2010 Springer Science+Business Media, LLC.